2009
DOI: 10.1111/j.1399-3038.2008.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fluticasone propionate 0.005% ointment in the long‐term maintenance treatment of children with atopic dermatitis: Differences between boys and girls?

Abstract: Efficacy and safety of fluticasone propionate 0.005% ointment in the long-term maintenance treatment of children with atopic dermatitis: Differences between boys and girls?Atopic dermatitis (AD) affects 8.9-20.4% of those born after 1970 (1). Despite the introduction of topical immune modulators, topical corticosteroids and emollients are still the mainstay of drug therapy in AD. Although the history of topical corticosteroids in dermatology covers half a century and many trials, available clinical studies do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 12 publications
3
64
0
4
Order By: Relevance
“…Two trials 105,106 reported that skin atrophy was not seen; however, one trial 108 reported that two participants showed skin changes often seen before atrophy (telangiectasia). Overall, a small number of adverse events assessed as being related to the trial medication were reported.…”
Section: Proactive Treatment Regimensmentioning
confidence: 99%
See 4 more Smart Citations
“…Two trials 105,106 reported that skin atrophy was not seen; however, one trial 108 reported that two participants showed skin changes often seen before atrophy (telangiectasia). Overall, a small number of adverse events assessed as being related to the trial medication were reported.…”
Section: Proactive Treatment Regimensmentioning
confidence: 99%
“…There was enough detail about the method of randomisation to allow assessment of the risk of bias in only six 97,102,103,107,108,110 out of 14 trials and all were assessed as being at low risk. There was enough detail about the method used to generate the allocation sequence to allow assessment of the risk of bias in only one 97 out of the 14 trials and this was assessed as low risk.…”
Section: Assessment Of Risk Of Bias For the New Studiesmentioning
confidence: 99%
See 3 more Smart Citations